2002
DOI: 10.1089/109493102760147204
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Face Gaze in Autism

Abstract: An eye-tracking study of face and object recognition was conducted to clarify the character of face gaze in autistic spectrum disorders. Experimental participants were a group of individuals diagnosed with Asperger's disorder or high-functioning autistic disorder according to their medical records and confirmed by the Autism Diagnostic Interview-Revised (ADI-R). Controls were selected on the basis of age, gender, and educational level to be comparable to the experimental group. In order to maintain attentional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 18 publications
1
42
0
1
Order By: Relevance
“…It has been demonstrated through behavioral observation and clinical accounts that individuals with ASD exhibit reduced attention to faces in general, and eyes in particular (Trepagnier et al 2002;Pelphrey et al 2002;Dalton et al 2005;Klin et al 2002). Results from several neuroimaging studies, furthermore, have provided evidence for atypical patterns of neural activation during viewing of unfamiliar faces by individuals with ASD (Critchley et al 2000;Hall, Szechtman et al 2003;Hubl et al 2003;Pierce et al 2001;Piggot et al 2004;Schultz et al 2000;Wang et al 2004), but normal patterns of neural activation for highly familiar faces (Aylward et al 2004;Pierce et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated through behavioral observation and clinical accounts that individuals with ASD exhibit reduced attention to faces in general, and eyes in particular (Trepagnier et al 2002;Pelphrey et al 2002;Dalton et al 2005;Klin et al 2002). Results from several neuroimaging studies, furthermore, have provided evidence for atypical patterns of neural activation during viewing of unfamiliar faces by individuals with ASD (Critchley et al 2000;Hall, Szechtman et al 2003;Hubl et al 2003;Pierce et al 2001;Piggot et al 2004;Schultz et al 2000;Wang et al 2004), but normal patterns of neural activation for highly familiar faces (Aylward et al 2004;Pierce et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the way in which an individual scans a face varies, depending on his or her experience with that face. Individuals with ASD, on the other hand, tend to have fewer fixations on the internal features of the face, particularly the eyes (Trepagnier et al 2002;Pelphrey et al 2002;Dalton et al 2005;Klin et al 2002). Klin et al (2002) used eye tracking methodology to demonstrate that while viewing dynamic images via a movie depicting naturalistic social scenes, individuals with ASD tend to spend more time looking at the mouth region of the face than the eyes.…”
Section: Eye Tracking and Familiar Facesmentioning
confidence: 99%
“…Children with autism, in contrast, are better at recognizing isolated facial features and partially obscured faces than typical children (Hobson, Ouston & Lee, 1988;Tantam et al, 1989) and show better performance on memory for the lower half of the face than the upper half during childhood (Langdell, 1978). Studies of visual attention to faces indicate that individuals with autism exhibit reduced attention to the core features of the face, such as the eyes and nose, relative to typical individuals (Klin, Jones, Schultz, Volkmar, & Cohen, 2002;Pelphrey et al, 2002;Trepagnier, Sebrechts, & Peterson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These claims are based on the large number of studies documenting reduced attention to faces (Hutt and Ounsted 1966;Trepagnier et al 2002;Riby and Hancock 2008;Sasson et al 2007;Bal et al 2010;Baranek 1999;Chawarska and Shic 2009;Osterling and Dawson 1994;Osterling et al 2002;Hernandez et al 2009) and/or atypical eye fixation in autism (as initially detailed in Kanner's first descriptions of autism, Kanner 1943Kanner , 1944; see also Joseph and Tanaka 2003;Riby and Hancock 2008;Boraston et al 2008;Sterling et al 2008;Jones et al 2008; for a review see Senju and Johnson 2009a). Klin et al (2002) assessed fixation patterns while participants observed emotional movie clips containing social interaction.…”
mentioning
confidence: 99%